PENDUGAAN UMUR SIMPAN TEPUNG PISANG (MUSA PARADISIACA) DALAM KEMASAN KOMERSIAL - Dewi Larasati; Murtiari Eva; Triyono Triyono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
This research was done in orderto predict shelf life of banana fruit flour (Musa poradisiacai in commercial packaging storage, using Accelerated Storage Studies reffered lo Arrhenius model. The commercial packaging using cloths bag, polyethylene film (0,005 mm thickness), and double polyethylene film (0,0 IO thickness). Each bags contains 50 gram samples. These samples were storaged indifferent condition, i.e. 30°C, 35°C and 45°C, in 80% relative humidity (RH) atmosphere for six weeks storage. Once in every week, the samples were evaluated on its critical water content. The results showed that the sample packaged in cloths bag can survive until 2.4 month storage. in polyethylene mono layer until 2.8 month and in double polyethylene until 4.2 month.